PENGEMBANGAN NANOPARTIKEL KETOPROFEN DENGAN TEKNIK SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) DAN UJI AKTIVITAS ANTIINFLAMASI - , M. Handoyo Sahumena ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ketoprofen is a non steroidal antiinflammatory drugs (NSAID) derives from propionic acid with the IUPAC name (RS)-2-(3-benzoylphenyl) propanoic acid. Ketoprofen has a very low solubility in water and thus affecting the absorption. Making ketoprofen into SNEDDS is one of the best way to solve the solubility problem. SNEDDS will spontaneously form nanoemulsion in digestive tract. The SNEDDS formula of ketoprofen was contained combination of oleic acid, tween 80, tween 20, and propylene glycol. The composition of tween 80 and tween 20 were determined with the aid of Design Expert 7.1.3 software. The nanoemulsion clarity was determined by transmittance measuring and the SNEDDS emulsification rate was characterized by emulsification time study. Average droplet size diameter, droplet size distribution, zeta potential, stability, in vitro dissolution profile, and in vivo anti-inflammatory tests were determined from the optimum formula. The SNEDDS optimum formula consists of 1 mL oleic acid